Treatment of Advanced Gingival Recession Secondary to Surgical Failure with Large Size Deepithelized Gingival Graft Associated with a Modified Tunnel Flap - Lingzhou Zhao; Yuan Gao; Yihan Xiao; Xinwei Tan; Xiaochen Li; Tianzheng Deng (Case Reports in Dentistry)
Objective. To describe the use of a large size deepithelized gingival graft (DGG) associated with full-split tunnel technique in a clinical case of advanced gingival recession secondary to surgical failure (GRSF). Clinical Considerations. The presented case report helped to achieve satisfactory root coverage, ideal keratinized tissue gain, improvement in soft tissue quality and esthetics, scar deformity correction, and vestibular depth deepening with a one-step procedure of large size DGG associated with full-split tunnel technique for a condition of deep gingival recessions of 7-11 mm caused by a failed bone implantation surgery. Conclusions. The large size DGG associated with full-split tunnel technique provided a versatile one-step procedure to obtain ideal results for advanced GRSF. Clinical Significance. GRSF that is generally associated with inadequate keratinized tissue and scar formation could be rather difficult to deal with. The large size DGG associated with full-split tunnel technique, as a one-step procedure, provided a predictable and practical treatment modality.